The Influence Of Employee Engagement, Work Environment And Organizational Learning On Organizational Commitment In Employees Of CV. Jodion Unggul Perkasa Sleman Regency - Lusei Lavendasari; Prayekti Prayekti; Nala Tri Kusuma (Universitas Trunodjoyo Madura, 2025)
This study aims to determine the effect of employee engagement , work environment, and organizational learning on organizational commitment in employees of CV. Jodion Unggul Perkasa Sleman Regency. The method used in this research uses quantitative methods. The population in this study were employees who worked at CV. Jodion Unggul Perkasa Sleman Regency using a sample of 103 respondents using purposive sampling technique. Data analysis used is multiple linear regression analysis. The results showed that employee engagement, work environment, and organizational learning have a positive and significant effect on organizational commitment. This study supports various theories that reveal that employee engagement factors, work environment, and organizational learning have a significant role in shaping organizational commitment. The implication of this research is expected to increase engagement for employees and create a conducive work environment which in turn will affect employee commitment to the organization. In addition, organizations need to ensure the availability of sufficient access to learning for employees, through training programs and skills development relevant to their duties in order to increase the loyalty and commitment of their employees.